Study of settlements carrying capacity in Jebres Subdistrict, Surakarta with das sein – das sollen approach - Desta Eka Fahrurozi; Berlian Warit Amalia; Lia Kusumaningrum; Desma Asty Pramudita; Gavriel Enos Berlin; Muhammad Nur Sulton; Nimas Wahyu Silaningtyas; Ulfi Hanum; Widhi Himawan; Winda Sagita Armadhan; Zahra Hanun (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The calculation of the carrying capacity of urban settlements is intended to determine the availability and status of environmental aspects that are utilized by the community. This study aims to examine the availability of environmental support aspects in Jebres District, Surakarta City through the das sein and das sollen approaches. The results of this study indicate that the availability of settlements and supporting aspects in the Jebres District are still able to support the demand for housing in 2018 and projections until 2055. Analysis through the expectation approach (das sein) for 100% decent settlements and the quality of the supporting aspects capable has not been fully realized concretely (das sollen). The availability of green open space (RTH) in Jebres District also does not meet the standards set by the government (30%) where the total area of ​​green open space in Jebres District is 23% of the total. The results of this study are related to the 3rd, 4th and 11th environmental principles. Keywords: carrying capacity, das sein-das sollen, environmental principles, green open space, settlements.